Current landscape of primary small bowel leiomyosarcoma: cases report and a decade of insights - Zhou, Junjie; Xu, Houyun; Hu, Jibo; Hong, Qiang; Yu, Xiping; Liu, Wei; Zhao, Jiaxin; Hu, Hongjie (Frontiers in Oncology, 2024)
The incidence of leiomyosarcoma (LMS) is about 4–5/100,000 individuals per year. LMSs occurring in the small bowel are even rarer, and their preoperative diagnosis is very difficult. We described two patients with pathologically confirmed small bowel LMS and analyzed their clinical and medical imaging features. Similar cases reported in English in Pubmed database over the past decade were reviewed and summarized. These tumors were categorized by the growth direction and relationship with the intestinal lumen into three types: intraluminal (n = 10), intermural (n = 3), and extraluminal (n = 7). Notably, among the three types of LMS, the intramural leiomyosarcoma stands out as a noteworthy subtype. Emerging evidence suggests that smaller tumor size (< 5 cm) and the intraluminal type may serve as favorable prognostic indicators, while the extraluminal type is associated with relatively poor prognosis. Furthermore, the integration of imaging features with CA125 and LDH biomarkers holds promise for potential diagnostic value in LMS.